Chronic early‐life stress increases cognitive impulsivity and D2 immunoreactivity in the nucleus accumbens of adult rats. Issue 4 (28th March 2022) - Laguna, Arturo; Lajud, Naima; Juárez, Jorge; Sanz‐Martin, Araceli
Abstract: Chronic early life stress (ECS) induced by limited bedding and nesting (LBN) material in rodents is a naturalistic stress model that mimics many of the behavioral and neural consequences of child abuse and neglect; however, the effect of ECS on adult impulsivity has never been studied. The aim of our work was to determine the effects of ECS on cognitive impulsivity and its relation to D2 immunoreactivity in the nucleus accumbens (NAc) and prefrontal cortex (PFC) of adult male rats. Sprague–Dawley rats were exposed to LBN from postnatal day 2 to 9. We evaluated dams' maternal behavior and offspring corticosterone levels. The rats' impulsive cognitive behavior was evaluated by a delay‐discounting task (transitional bridge) on P70, and we evaluated D2 receptors by immunostaining. Our results indicated that ECS affected maternal behavior in the dams and increased pups' corticosterone levels at P9, but not in adults. ECS rats showed lower frequencies of choosing the delayed reinforcer and shorter latencies to cross on the delay‐discounting task. In addition, ECS rats showed increased D2 immunoreactivity in the NAc when compared with controls. Our data suggest that ECS can cause impulsive behaviors in adult rats characterized by less convenient choices, likely related to an increase in D2 receptors in the NAc. These findings could contribute to our understanding of the effects of child abuse and neglect on impulsive behavior.